Antagonism of Trichoderma spp. strains against pea (Pisum sativum L.) Fusarium wilt caused by Fusarium oxysporum f. sp. pisi. (2017)
The antagonistic effectiveness of native strains of Trichoderma spp. on Fusarium oxysporum f. sp. pisi. in vitro, greenhouse and field conditions, were evaluated. in vitro conditions, the antagonistic capacity of 12 strains of Trichoderma spp., C2, C7, C12 and C21 strains, exhibited a better behavior measured by the following variables: inhibition halo and mycelial growth. In greenhouse conditions, the four strains, which showed the best in vitro antagonistic behavior, were evaluated using a DIA experimental design with factorial arrangement for three factors, which corresponded to strain, concentration and dose. The results of this evaluation, showed that C12 and C21 strains at doses of 20 mL, and at concentrations of 108 and 106 conidia.mL-1, respectively. The best antagonistic response was determined by variables as follows: plant height, fresh root weight and incidence. Under field conditions, the evaluations were carried out in the municipalities of Ipiales, Pupiales and Gualmatán, in the department of Nariño, Colombia. In each location, a BCA experimental design was used with four treatments and five replicates, treatments were as follows: C12 strains at 108 concentration, C21 at 106 concentration, chemical control and absolute control. In Gualmatan location, C12 and C21 strains, showed no antagonistic capacity, whereas in Ipiales and Pupiales locations, strain C12, presented a lower incidence of F. oxysporum than the control, but with no effect on yields. In Pupiales location, C21 strain surpassed in performance to the control treatment, even though the two treatments had similar incidence.